A Superconducting Dual‐Channel Photonic Switch. Issue 29 (5th June 2018) - Srivastava, Yogesh Kumar; Manjappa, Manukumara; Cong, Longqing; Krishnamoorthy, Harish N. S.; Savinov, Vassili; Pitchappa, Prakash; Singh, Ranjan
Abstract: The mechanism of Cooper pair formation and its underlying physics has long occupied the investigation into high temperature (high‐ T c ) cuprate superconductors. One of the ways to unravel this is to observe the ultrafast response present in the charge carrier dynamics of a photoexcited specimen. This results in an interesting approach to exploit the dissipation‐less dynamic features of superconductors to be utilized for designing high‐performance active subwavelength photonic devices with extremely low‐loss operation. Here, dual‐channel, ultrafast, all‐optical switching and modulation between the resistive and the superconducting quantum mechanical phase is experimentally demonstrated. The ultrafast phase switching is demonstrated via modulation of sharp Fano resonance of a high‐ T c yttrium barium copper oxide (YBCO) superconducting metamaterial device. Upon photoexcitation by femtosecond light pulses, the ultrasensitive cuprate superconductor undergoes dual dissociation–relaxation dynamics, with restoration of superconductivity within a cycle, and thereby establishes the existence of dual switching windows within a timescale of 80 ps. Pathways are explored to engineer the secondary dissociation channel which provides unprecedented control over the switching speed. Most importantly, the results envision new ways to accomplish low‐loss, ultrafast, and ultrasensitive dual‐channel switching applications that are inaccessible through conventional metallic and dielectric based metamaterials. Abstract : Upon irradiation with an optical pulse, YBCO superconductors show dual dissociation–relaxation windows within a single superconductivity restoration cycle resulting in dual‐channel, ultrafast switchable metadevices. Dual switching channels exist due to primary and secondary dissociation of Cooper pairs, which eventually enable two distinct pathways for the modulation of terahertz waves at picosecond time scale.